Diseño de una faja transportadora de 150 m para 60 t/h de Bagazo de Caña de Azúcar. - Villacorta Corcuera, Melfin Yancarlos (2020)
The objective of this work is to design and select the mechanical components of a 150 m long conveyor belt, for the transport of sugarcane bagasse at a capacity of 60 t / h in the company Agrolmos SAA, in order to evacuate said material to composting wells. This work is based on the design methodology of conveyor belts by the " Conveyor Equipment Manufacturers Association " (CEMA) and the use of the "Solidworks" engineering program as a tool for static analysis of the structure of the conveyor. In Chapter I, it deals with the problematic reality of the company, as well as the reason why we are encouraged to design a conveyor belt, in order to facilitate transport in bulk and continuously at a lower cost. In Chapter II, try to explain step by step the calculation methodology based on the CEMA manual; where the use of equations, graphs and tables is exposed, to determine operating parameters (speed, power) and select the mechanical components of the conveyor (idlers, pulleys, belt, drive system, cleaner, transmission, support structure). In chapter III, the sequence to follow for the calculation and selection of components is explained; Information was collected (belt capacity, material to be transported, height and length of the conveyor), width and belt speed were determined, finally the parameters and selection of conveyor components were calculated. In Chapter IV, the results are presented as belt width (30”), belt speed (1.71 m / s), drive power (20 hp), etc. and a static analysis is carried out on the conveyor structure with the Solidworks program.